Population Characteristics of Smallmouth Bass (Micropterus dolomieui) in the Plover and Red Cedar Rivers, Wisconsin - Paragamian, Vaughn L. (University of Wisconsin-Stevens Point, 1973)
Population size, standing crop, movement, food habits, growth rate, age class composition and total annual mortality rate, were determined for smallmouth bass (Micropterus dolomieui) in the Plover River, Wisconsin. The same population characteristics plus exploitation, annual natural mortality and fishing rates and critical size were determined for the species in the Red Cedar River, Wisconsin. Fin clipped or tagged fish were recaptured in electrofishing operations in both rivers and from a partial creel census in the Red Cedar River. The capture of 243 and recapture of 55 smallmouth bass of 110 to 492 mm in the Plover River yielded a population estimate of 118 smallmouth bass/ha or 17.5 kg/ ha in three study areas. In the Red Cedar River, the capture of 791 and recapture of 166 smallmouth bass of 73 - 448 mm provided estimates of 132 fish/ha or 15.1 kg/ha. Recaptures indicated restricted movement of the species. Major constituents of the diet in summer were fish, crayfish, and aquatic insects. Frequencies of occurrence were 48% fish and 24% crayfish in stomachs of 25 Plover River smallmouth bass over 135 mm long and in the Red Cedar River, 40% crayfish, 26% fish and 24% aquatic insects in 50 stomachs of smallmouth bass over 162 mm long. Stomachs of 16 smallmouth bass of 73 to 136 mm in the Red Cedar River contained aquatic insects. In laboratory predation studies, order of preference of prey to smallmouth bass was common shiner, hornyhead chub and white sucker. Growth of Plover River smallmouth bass was similar to that of other populations of smallmouth bass in the U.S., whereas growth in the Red Cedar River exceeded that of many other populations. Mean lengths for ages I through IX in the Plover River were 91, 158, 220, 297, 366, 410, 440, 455, and 476 mm, respectively, and in the Red Cedar River, 100, 190, 274, 329, 383, 407, 424, and 444 mm for ages I through VIII, respectively. Total annual mortality rate,determined from catch curves were 65% for ages I through VI and 55% for ages II through VIII in the Plover and Red Cedar Rivers, respectively. Exploitation rates, of tagged smallmouth bass 200 mm or greater in the Red Cedar River, when corrected for nonreturn of tags and tag loss, was estimated to be 29% from the opening of the angling season on 12 May to the end of September. The angler's catch during the same period when estimated from the creel census data was 21 fish/ha (5.1 kg/ha) or 34% of the population estimate. Annual natural mortality was 31% and annual fishing mortality rate was 35% for smallmouth bass 200 mm and larger. Anglers caught smallmouth bass at an estimated rate of 0.07 fish/hour, mean length in the catch was 262 mm and 78% of the catch was made up of bass of ages II and III and 95% of ages II through V. Critical size, the size at which a year class reaches its maximum biomass, was estimated to be between 383 and 407 mm, ages V and VI, for smallmouth bass in the Red Cedar River. Calculation of equilibrium yield indicated that weight harvested could be increased by 36% if there were a 232 mm length on the fishery and by 44% with a 302 mm length limit.